2017
DOI: 10.1007/s00586-017-4979-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between pain sensitivity in the hand and outcomes after surgery in patients with lumbar disc herniation or spinal stenosis

Abstract: Purpose To investigate the association between pain sensitivity in the hand pre-surgery, and patient-reported outcomes (PROs) in function, pain and health pre-and postsurgery in patients with disc herniation or spinal stenosis. Methods This is a prospective cohort study with 82 patients. Associations between pressure-, cold-and heat pain threshold (PPT, CPT, HPT) in the hand pre-surgery and Oswestry, VAS pain, EQ-5D, HADS, and Self-Efficacy Scale, pre-and three months post-surgery; were investigated with linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nervus Medianus) was included in the analyses. [56,30] First, the electrical pain threshold was determined. Stimuli were given as a constant current rectangular pulse train consisting of 5 pulses at 250 Hz, each lasting 0.5 ms. For determining the threshold, stimulation started at 0 mA and was gradually increased by steps of 0.5 mA until the patients experienced the stimulus as unpleasant.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Nervus Medianus) was included in the analyses. [56,30] First, the electrical pain threshold was determined. Stimuli were given as a constant current rectangular pulse train consisting of 5 pulses at 250 Hz, each lasting 0.5 ms. For determining the threshold, stimulation started at 0 mA and was gradually increased by steps of 0.5 mA until the patients experienced the stimulus as unpleasant.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Furthermore, there has been a growing interest in endogenous nociceptive modulation in chronic pain research. [28][29][30][31][32] Endogenous pain modulatory processes encompass various actions that the central nervous system can use to reduce (e.g. inhibition) or augment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective complaint of poor outcome is also well documented in the broader pain literature, with individuals reporting a range of difficulties associated with sensory pain including poorer physical functioning, self-efficacy, cognition and mood (Lindbäck et al, 2017; Mazza et al, 2018). Similarly, it has been shown that affective distress in chronic pain patients is associated with poorer quality of life and cognitive complaint (Muñoz & Esteve, 2005; Rada et al, 2016).…”
mentioning
confidence: 99%